Direct use of 1, 3-dienes for the allylation of ketones via catalytic hydroindation. Issue 10 (6th February 2020) - Suzuki, Itaru; Yagi, Kensuke; Miyamoto, Shinji; Shibata, Ikuya
Abstract : In this study, in situ catalytically generated allylic indium from 1, 3 dienes and InCl2 H was developed for use in the allylation of ketones. Abstract : In this study, in situ catalytically generated allylic indium from 1, 3 dienes and InCl2 H was developed for use in the allylation of ketones. This protocol resulted in the unprecedented establishment of a successive combining of quaternary C–C bonds, which could then be applied to many types of ketones. Other branched 1, 3 dienes and vinyl cyclopropanes, could also be coupled with ketones in a reaction where CuH would not be applicable.